Existence of Solutions for Impulsive Neutral Semilinear Evolution Equations with Nonlocal Conditions - Agarwal, R. P.; Leiva, H.; Riera, L.; Lalvay, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
Fractional Power Spaces and Karakostas' Fixed Point Theorem were used to prove the existence and uniqueness of solutions for a semilinear neutral evolution equation with impulses and nonlocal conditions in a Banach space. As an application of our main result, we consider a neutral type Burgers' equation.